2000
DOI: 10.1023/a:1007022428041
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 1. The role of synaptophysin in the exocytotic release of dopamine (DA) was examined in Xenopus laevis oocytes injected with rat brain mRNA. 2. The mRNA-injected oocytes showed DA uptake which depended on the incubation time and external DA concentrations. 3. Stimulation with KCl (10-50 mM) of mRNA-injected oocytes preloaded with DA evoked external Ca2+ -dependent release of DA. The noninjected and water-injected oocytes did not produce uptake of DA and stimulation-evoked release of DA. 4. The high-KCl (50 mM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It is uncertain how this interaction works, Gordon et al propose a role for synaptophysin during SV recycling, retrieving synaptobrevin during SV endocytosis [59]. The decrease in synaptophysin points to a decrease in synaptic density, its expression has been linked both to DA release as well as to motor performance in a mouse model for PD [60, 61]. We postulate that a higher α-SYN load at the level of the synapse induces presynaptic alterations, resulting in aggravated motor dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain how this interaction works, Gordon et al propose a role for synaptophysin during SV recycling, retrieving synaptobrevin during SV endocytosis [59]. The decrease in synaptophysin points to a decrease in synaptic density, its expression has been linked both to DA release as well as to motor performance in a mouse model for PD [60, 61]. We postulate that a higher α-SYN load at the level of the synapse induces presynaptic alterations, resulting in aggravated motor dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in Xenopus reconstitution systems suggested a central role for synaptophysin in neurotransmitter release using either its overexpression or injection of antisense or antibodies to perturb its function [5][6][7][8]. However, when synaptophysin knockout mice were generated, they were viable and had no obvious defects in neurotransmitter release [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…PSD-95 interacts with various binding partners, such as associated synaptic proteins, ion channels, and cytoskeletal elements, to form a complex network that stabilizes and regulates synaptic function, transmission and formation and maintenance of dendritic spines, receptor tra cking, and synaptic signaling and plasticity mechanisms [45][46][47][48] . Synaptophysin is involved in synaptic plasticity 49 , and in synaptic vesicle exocytosis 50,51 . It is an integral component of the synaptic vesicle membrane and interacts with other proteins to regulate vesicle fusion with the presynaptic membrane, thereby facilitating the release of neurotransmitters into the synapse [52][53][54] .…”
Section: Discussionmentioning
confidence: 99%